SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KARYA INOVASI TERBAIK DENGAN METODE WEIGHTED PRODUCT BERBASIS WEBSITE PADA PT. JASA MARGA (PERSERO) TBK CABANG JAKARTA - TANGERANG - CENGKARENG - Brian - Pangestu; Frencis Matheos Sarimole (CKI ON SPOT, 2019)
The purpose of this study was to design a decision support system in evaluating the best innovation works using website-based weighted product method at PT. Jasa Marga (Persero) Tbk Jakarta - Tangerang - Cengkareng Branch. The method in collecting data by conducting interviews, observation and literature study, then the method of analysis uses the Waterfall Approach System Development Life Cycle (SDLC) system, in the system design method using object-based methods namely Unified Modelling Language (UML) consisting of Use case diagrams , Activity diagram, Sequence diagram and Class diagram, then the decision support system method used is the Weighted Product method, and the testing method used is Blackbox Testing. The design of the program uses PHP version 5.6.37 programming language and Adobe Dreamweaver CS6 version 11.0 as a text editor, and MySQL version 4.8.2 as a database. The results of this study can be expected to assist infacilitating and reducing the time needed in the decision-making process, making judgment decisions more accurate in recording and calculation, minimizing data loss, saving costs for printing costs, andmaximizing company performance.